Pengaruh Financial Distress, Leverage, dan Profitabilitas Terhadap Konservatisme Akuntansi - Iddha Wahyu Dwi Putra; Vita Fitria Sari (Universitas Negeri Padang, 2020)
This study aims to prove empirically the effect of financial distress, leverage and profitability on accounting conservatism. The sample selection in this study used a purposive sampling method with various criteria according to the objectives of the study. The total samples used as research objects in this study were 60 manufacturing companies. The data analysis used in this research is descriptive statistics using logistic regression analysis techniques. The results of this study can prove that financial distress has no effect on accounting conservatism. A regression coefficient of -0.171 of one unit will reduce accounting conservatism by 0.171 units. The significance value (sig) of 0.389> greater than 0.05, it can be concluded that the hypothesis H1 is rejected. In addition, this study can also prove empirically that leverage has a positive effect on accounting conservatism with a sig value of 0.026 <0.05. Then it can be concluded that the H2 Hypothesis is Accepted. Meanwhile, the profitability variable has an effect on accounting conservatism with a significance value (sig) of 0.022 less than 0.05. So it can be concluded that the H3 Hypothesis is Accepted. Suggestions for further research are expected to increase the number of research samples and also the year of observation. Can also use other variables that are used to measure accounting conservatism. While the overall contribution in this study was 5.7% while 94.3% was influenced by other factors or other variables not included in this study.